Chinese Ethnic Youth's Voting Behavior in the 2018 Palembang Mayoral Election - Khairunnas, Khairunnas; Agustino, Leo; Sumadinata, Widya Setiabudi (Journal of Moral and Civic Education, 2018)
The emergence of demographic issues makes research related to the behavior of beginner voters very interesting to do, some studies have managed to find a tendency for beginner voter behavior, and several other studies have also succeeded in finding trends in voting behavior against ethnic identity. Therefore researchers are interested in discussing and describing the tendency of voter behavior in certain age categories which are also clashed with ethnicity factors. Chinese ethnicity is an ethnic minority that has a long history on the Indonesian political stage, and the city of Palembang is one of the cities in Indonesia that has left a lot of evidence of the history of Chinese civilization, even from the time of the Srivijaya Empire. This study aims to determine the behavioral trends of choosing Chinese Ethnic Youth in the Mayor and Deputy Mayor of Palembang in 2018. The method used in this study is a quantitative method with a survey design. The unit of analysis of this study was ethnic Chinese youth who were members of the Indonesian Chinese Youth Association (IPTI) in Palembang City. This study uses a voter behavior approach with an analysis of three models, namely sociological, psychological and rational choices. Based on the results of the research in the field it can be concluded that the behavior of choosing Chinese Ethnic Youth in the Mayor and Deputy Mayor of Palembang in 2018 has a tendency towards psychological and rational voting behavior. Psychologically, the behavior of choosing ethnic Chinese youth tends to be influenced by indicators of the influence of campaigns and figures of candidates, while rationally tends to be influenced by the leadership performance indicators of candidates in the previous period. Keywords: voting behavior, youth, Chinese ethnic group, 2018 Palembang mayoral election Abstrak Munculnya isu demografi membuat penelitian terkait perilaku pemilih pemula sangat menarik untuk dilakukan, beberapa penelitian berhasil menemukan kecenderungan perilaku pemilih pemula, dan beberapa penelitian lainnya juga berhasil menemukan kecenderungan perilaku memilih yang dilatarbelakangi identitas etnis. Oleh sebab itu peneliti tertarik membahas dan menguraikan kecenderungan perilaku pemilih dalam kategori usia tertentu yang juga dibenturkan dengan faktor etnisitas. Etnis Tionghoa merupakan etnis minoritas yang memiliki sejarah panjang di panggung politik Indonesia, dan Kota Palembang merupakan salah satu kota di Indonesia yang banyak meninggalkan bukti sejarah peradaban Tionghoa, bahkan sejak zaman Kerajaan Sriwijaya. Penelitian ini bertujuan untuk mengetahui kecenderungan perilaku memilih Pemuda Etnis Tionghoa pada Pemilihan Walikota dan Wakil Walikota Palembang tahun 2018. Metode yang digunakan pada penelitian ini adalah metode kuantitatif dengan rancangan survei. Unit analisis penelitian ini adalah pemuda Etnis Tionghoa yang tergabung dalam Ikatan Pemuda Tionghoa Indonesia (IPTI) Kota Palembang. Penelitian ini menggunakan pendekatan perilaku pemilih dengan analisis tiga Model, yakni Model sosiologis, psikologis dan pilihan rasional. Berdasarkan hasil penelitian di lapangan dapat disimpulkan bahwa perilaku memilih Pemuda Etnis Tionghoa pada Pemilihan Walikota dan Wakil Walikota Palembang tahun 2018 memiliki kecenderungan perilaku pemilih psikologis dan rasional. Secara psikologis perilaku memilih pemuda Etnis Tionghoa cenderung dipengaruhi oleh indikator pengaruh kampanye dan ketokohan calon, sedangkan secara rasional cenderung dipengaruhi oleh indikator prestasi kepemimpinan calon pada periode sebelumnya. Kata kunci: perilaku memilih, pemuda, etnis Tionghoa, pilkada kota Palembang 2018